Recent advances in treatment of allergic rhinitis in children - Mohamed Sayed Badr; Amr Albadrawy; Mosaad Abdelaziez (Cairo : Mohamed Sayed Badr, 2009)
Allergic rhinitis may appear in infancy and the diagnosis is generally established by the age of 6 years its prevalence peaks late in childhood and then may decrease later on allergic rhinitis resolves in only ten to twenty percent of children within the age of ten years
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of E.N.T
Issued also as CD
Keywords: Advances allergic rhinitis treatment; Children